Employment Status of Women in the Seafood Processing Sector of Gujarat - Jeyanthi, P.; Gopal, Nikita; Murty, L. N.; Geethalakshmi, V. (Fishery Technology, 2025)
More than 75% of the workforce in the seafood processing sector in India are women. This study explored the employment status of women in seafood processing sector in Gujarat, which is one of the largest states in terms of number of seafood processing plants and quantity of seafood exports. The male to female ratio in the industry was 1:1.74 and 1:1.66 in the contractual and permanent employment categories respectively. About 63% of the respondents were under 30 years of age and unmarried. The monthly wages of women workers at the floor level was ` 2594/- which is much lower than the minimum wages prescribed by the Gujarat State for unskilled workers which is ` 214.90 day-1. It was observed that the major determinants of women’s employment in the sector were their educational status and wages. The wage of worker in processing sector showed significant positive relationship with age, education and work experience.